Jefferson vs. the Patent Trolls : A Populist Vision of Intellectual Property Rights - Matsuura, Jeffrey H., 1957- (Book collections on Project MUSE., 2008)
Jefferson was in a unique position to understand the issues of intellectual property rights. As a scientist, author, and inventor, he was a prolific creator. He was also a tireless consumer of others' works. As America's first patent commissioner, he decided which ideas merited protection and effectively created the patent review process. Jeffrey Matsuura profiles Jefferson's diverse and substantial experience with these issues and discusses the lessons Jefferson's efforts offer us today, as we grapple with many of the same challenges of balancing IP rights against an effort to foster creativity and innovation. --from publisher description.